The properties investigation of the faradaic supercapacitor electrode formed on foamed nickel substrate with polyvinyl alcohol using - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2017)
The electrode materials for positive electrodes of hybrid supercapacitors were deposited on the nickel foam substrate using cathodic template method. It has been demonstrated that prepared materials are composed of polyvinyl alcohol and X-ray amorphous α-like nickel hydroxide with a large number of lattice defects, that have a flat morphology with a grid of cracks. The optimal deposition times were found to be 10 and 20 minutes. It has also been demonstrated that the greatest effect on the capacity of nickel foam substrates was caused by the treatment itself and to not by its duration or polarization with the cathodic current. It has been demonstrated that with such deposition method, the resulting capacity is constituted by two components – the capacity of PVA-Ni(OH)2 composite material and capacity of the nickel foam substrate. The maximum specific capacity obtained at a current density of 320 mA/cm2 is 2.26 F/cm2. The maximum substrate capacity was achieved after treatment with KNO3 solution for 10 minutes and is 1.58 F/cm2 at a current density of 160 mA/cm2